Evaluating Alternative Police Responses to Spouse Assault in Colorado Springs: an Enhanced Replication of the Minneapolis Experiment, 1987-1989 - Black, Howard ([Verlag nicht ermittelbar], 1994)
The purpose of this study was to replicate an experiment in Minneapolis (MINNEAPOLIS INTERVENTION PROJECT, 1986-1987 [ICPSR 9808]) testing alternative police response to cases of spouse assault, using a larger number of subjects and a more complex research design. The study focused on how police response affected subsequent incidents of spouse assault. Police responses studied included arrest, issuing emergency protection orders, referring the suspect to counseling, separating the suspect and the victim, and restoring order only (no specific action). Data were obtained through initial incident reports, counseling information, and personal interviews. Follow-up interviews were conducted at three- and six-month periods, and recidivists were identified through police and court record checks. Variables from initial incident reports include number of charges, date, location, and disposition of charges, weapon(s) used, victim injuries, medical attention received, behavior towards police, victim and suspect comments, and demographic information such as race, sex, relationship to victim/offender, age, and past victim/offender history. Data collected from counseling forms provide information on demographic characteristics of the suspect, type of counseling, topics covered in counseling, suspect's level of participation, and therapist comments. Court records investigate victim and suspect criminal histories, including descriptions of charges and their disposition, conditions of pretrial release, and the victim's contact with pretrial services. Other variables included in follow-up checks focus on criminal and offense history of the suspect. The data collection includes separate data files for the original, second, and final versions of some of the forms that were used.